Factores de riesgo asociados al síndrome metabólico en mujeres que trabajan en sección de comida Mercado Mayorista Loja - Alvarez Rivas, Dalila Francisca (2015)
This study was aimed to identify the main risk factors associated with the development of metabolic syndrome in women working in food industry section two. To guide ladies on its prevention and control; a descriptive study was conducted in the Wholesale market of the city of Loja where 250 ladies work, and then were taken into account 75 ladies between age 45 to 65, who work in the food sector section two, it was performed a survey sheet whose data: height and weight, blood pressure and laboratory tests HDL, LDL, triglycerides, glucose and cholesterol were noted. The results were as follows: a large percentage (60%) with a circumference waist greater to 90 centimeters, to a lesser extent (52%) are overweight, more than half (60%) had HDL altered disease, the most stood out disease was the arterial hypertension (63%), the (57%) every six months medical controls is performed. Another important result is that the age group which is mostly present the metabolic syndrome was at age 45-50 years and who have a family history of diabetes mellitus, few ladies made short walks once a month which is not beneficial for their health. KEYWORDS: dyslipidemia, risk factors, metabolic